Colorectal Cancer Screening Uptake: Differences Between Rural and Urban Privately-Insured Population - Alyabsi, Mesnad; Meza, Jane; Islam, K. M. Monirul; Soliman, Amr; Watanabe-Galloway, Shinobu (Frontiers in Public Health, 2020)
Earlier studies investigated rural-urban colorectal cancer (CRC) screening disparities among older adults or used surveys. The objective was to compare screening uptake between rural and urban individuals 50-64 years of age using private health insurance. Data were analyzed from 58,774 Blue Cross Blue Shield of Nebraska (BCBSNE) beneficiaries. Logistic regression was used to assess the association between rural-urban and CRC screening use. Results indicate that rural individuals were 56% more likely to use the Fecal Occult Blood Test (FOBT) compared with urban residents, but rural females were 68% less likely to use FOBT. Individuals with few Primary Care Physician (PCP) visits and rural-women are the least to receive screening. To enhance CRC screening, a policy should be devised for the training and placement of female PCP in rural areas. In particular, multilevel interventions, including education, more resources, and policies to increase uptake of colorectal cancer screening, are needed. Further research is warranted to investigate barriers to CRC screening in rural areas.